2017
DOI: 10.1039/c7ob01803g
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective bioreduction of benzo-fused cyclic ketones with engineered Candida glabrata ketoreductase 1 – a promising synthetic route to ladostigil (TV3326)

Abstract: Biocatalysis has been recently emerging as a promising alternative to traditional chemical synthesis because of its "green" characteristics and comparable selectivities, which accord with the concept of sustainable development and demand for asymmetric synthesis. In this study, whole-cell biocatalysts containing glucose dehydrogenase (GDH) and Candida glabrata ketoreductase 1 (CgKR1) variants were constructed. These biocatalysts were applied to the reduction of benzo-fused cyclic ketones and showed good to hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Similarly, Ou-Yang and coworkers 32 reported that mutations at residues Phe92, Tyr208, Met144, Phe145 of CgKR1, which are important for the binding pocket, afforded engineered CgKR1s with high activity and stereoselectivity towards benzo-fused cyclic ketones. Particularly, the whole-cell biocatalysts prepared by the co-expression of CgKR1 variants and GDH displayed excellent stereoselectivity (>99.9% ee) in the reduction of N -ethyl- N -methyl-2-(3-oxo-2,3-dihydro-1 H -inden-5-yl) acetamide, the key intermediate of the anti-Alzheimer drug ladostigil (TV3326).…”
Section: Enzyme Engineeringmentioning
confidence: 90%
“…Similarly, Ou-Yang and coworkers 32 reported that mutations at residues Phe92, Tyr208, Met144, Phe145 of CgKR1, which are important for the binding pocket, afforded engineered CgKR1s with high activity and stereoselectivity towards benzo-fused cyclic ketones. Particularly, the whole-cell biocatalysts prepared by the co-expression of CgKR1 variants and GDH displayed excellent stereoselectivity (>99.9% ee) in the reduction of N -ethyl- N -methyl-2-(3-oxo-2,3-dihydro-1 H -inden-5-yl) acetamide, the key intermediate of the anti-Alzheimer drug ladostigil (TV3326).…”
Section: Enzyme Engineeringmentioning
confidence: 90%